The life span of a print textbook: An investigation in the utility of aging textbook collections in academic libraries. Issue 1 (2nd January 2020) - McHale, Christopher
Abstract: This paper will use circulation data to explore usage trends for physical textbooks in an academic library over a sustained period of time. Conclusions will be drawn from the analysis to determine the usefulness of aging physical textbook collections in academic libraries and inform recommendations for efficient models of lending and management.